2021
DOI: 10.1177/09763996211003379
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Crime Against Women in India: A Spatial Panel Data Regression Analysis

Abstract: Gender discrimination has been an important socio-economic and cultural issue in Indian backdrop; though India is one of the fastest-growing nations in the world but she has ranked 108th (out of 144 countries) in 2016 on the global gender gap index. In order to explore the determinants of crimes (such as dowry death, rape, molestation and torture) in India, we consider 24 states and five time points (over 1995–2015). Rank correlation over time clearly suggests that states exhibiting higher incidence of molesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…Cyber Cafe10. It is a very common phenomenon that essential data of internet surfers is casually disclosed by cybercafé owners and then used for illicit commitments [1]. violations occur more frequently among humans If guardianship (Holt & Bassler, 2008) When these three key elements intersect, harm occurs resulting speech or violent expressions there is a high chance of such crimes taking place [7].…”
Section: Crime Against Women In Indiamentioning
confidence: 99%
“…Cyber Cafe10. It is a very common phenomenon that essential data of internet surfers is casually disclosed by cybercafé owners and then used for illicit commitments [1]. violations occur more frequently among humans If guardianship (Holt & Bassler, 2008) When these three key elements intersect, harm occurs resulting speech or violent expressions there is a high chance of such crimes taking place [7].…”
Section: Crime Against Women In Indiamentioning
confidence: 99%
“…Dowry death and molestation feature a positive association with rape and torture. It is also notable that cybercrimes are also increasing day by day because of the increased accessibility of various web media platforms [7]. In India, it has been observed that the overall crime rate has declined over the last two decades, but crime against women has increased [8].…”
Section: Introductionmentioning
confidence: 99%
“…At the state level, gender justice is determined by various state policies, while at the family level, gender equality is related to the power relations between men and women. One of the efforts to achieve gender justice is to increase women’s opportunities in education and work (Bhattacharyya et al, 2021; Mishra et al, 2020). The current study seeks to uncover how the power relations between husband and wife in dual-career families experience domestic violence.…”
Section: Introductionmentioning
confidence: 99%
“…Gender equality is very important for economic growth in Asian countries (Mishra et al, 2020), and gender discrimination has been an imperative socio-economic and cultural issue against women (Bhattacharyya et al, 2021). Therefore, researching domestic violence or violence against women (VAW) is important because of an escalation in the number of domestic violence cases (Indonesian National Commission on Violence Against Women, 2019).…”
Section: Introductionmentioning
confidence: 99%